The Characterization of Two-Component System PmrA/PmrB in Cronobacter sakazakii - Hua, Jingjing; Jia, Xiangyin; Zhang, Liang; Li, Yanyan (Frontiers in Microbiology, 2020)
Cronobacter sakazakii is an opportunistic Gram-negative pathogen that could cause meningitis and necrotizing enterocolitis. Several Gram-negative bacteria use the PmrA/PmrB system to sense and adapt to environmental change by resisting to cationic antimicrobial peptides of host immune systems. PmrA/PmrB two-component system regulates several genes to modify LPS structure in bacterial outer membrane. The role of PmrA/PmrB of C. sakazakii has been studied within the current study. The results suggest that the PmrA/PmrB plays a crucial role in modifying LPS structure, cationic antimicrobial peptides susceptibility, cell membrane permeability and hydrophobicity, and invading macrophage.